Batik discharge printing on silk, polyester and polyester/cotton blends / Wan Yunus Wan Ahmad ... [et al.] - Wan Ahmad, Wan Yunus; Ahmad, Mohd Rozi; Abdul Kadir, Muhammad Ismail; Muhammad, Rafizan (2004)
Malaysian batik has traditionally used wax as a physical resist to create designs on fabrics from cotton, silk and rayon. Discharge printing style is chosen because it is able to produce printed effects that would otherwise be virtually impossible to obtain by conventional printing style on polyester and polyester/cotton blend fabrics as "new" batik fabrics as well as traditional batik fabrics. Polyester and polyester/cotton blend fabrics should be considered as alternative fabrics for batik application because of their competitiveness in price, durability and colour fastness in comparison with traditional batik fabrics of cotton, silk and rayon. The printing techniques carried out were screen printing, block printing (cap), canting and brush. The fixation methods applied on the printed fabrics were dry heat at 150®C for three minutes and dried under the sun for one hour at a temperature of around 35°C. The result of different printing techniques and different methods of fixation were compared.